Planning in Cold War Europe : Competition, Cooperation, Circulations (1950s-1970s) - Christian, Michel 1977- (Rethinking the Cold War, 2018)
This volume aims at enlarging our understanding of planning, engineering and more generally regulation ideas by looking at possible forms of mutual interest, circulation of idea and models in a “pan’european” perspective. Contributions will emphasize the role played by actors from both sides of Europe at the micro- as well as macro-level and will highlight the role played by international organizations as fora and platforms where ideas and know-how were exchanged. The volume will also look at development projects in the developing countries as a field where European conceptions of planned development were competing but also converging especially in the eyes of the countries who benefited from these policies